Heritable Gene Regulation in the CD4:CD8 T Cell Lineage Choice - Issuree, Priya D. A.; Ng, Charles P.; Littman, Dan R. (Frontiers in Immunology, 2017)
The adaptive immune system is dependent on functionally distinct lineages of T cell antigen receptor αβ-expressing T cells that differentiate from a common progenitor in the thymus. CD4+CD8+ progenitor thymocytes undergo selection following interaction with MHC class I and class II molecules bearing peptide self-antigens, giving rise to CD8+ cytotoxic and CD4+ helper or regulatory T cell lineages, respectively. The strict correspondence of CD4 and CD8 expression with distinct cellular phenotypes has made their genes useful surrogates for investigating molecular mechanisms of lineage commitment. Studies of Cd4 and Cd8 transcriptional regulation have uncovered cis-regulatory elements that are critical for mediating epigenetic modifications at distinct stages of development to establish heritable transcriptional programs. In this review, we examine the epigenetic mechanisms involved in Cd4 and Cd8 gene regulation during T cell lineage specification and highlight the features that make this an attractive system for uncovering molecular mechanisms of heritability.